Hibridación natural y métodos de polinización manual en Phaseolus coccineus L. - Muruaga Martínez, José S.=700 1 Cárdenas Ramos, Francisco; Acosta Gallegos, Jorge A.
Sumario (Es)
9 ref.
Keywords: PHASEOLUS COCCINEUS; HIBRIDACION; POLINIZACION LIBRE; VARIACION GENETICA